Characterizing the Early Bronze III–IVA1 pottery of the northern Levant through typological and petrographic analyses. The case study of Tell Mardikh/Ebla and Tell Tuqan (Syria). (3rd May 2020) - Vacca, Agnese
Abstract : This article uses the results of petrographic analyses carried out on the Early Bronze (EB) III–IVA1 ceramics from Ebla and Tell Tuqan, combined with the functional and morphological classification of the ceramic repertoire, with the dual aims of building a regional ceramic chronology and analysing pottery production at both sites in a diachronic perspective. These datasets indicate, on the one hand, a continuous trend in ceramic production between the EB III and EB IVA1–2 periods, both in term of vessel shapes and in the selection of pastes employed in pottery manufacture. On the other hand, some substantial changes can be detected, suggesting a growing degree of standardization in manufacturing processes and a functional specialization of the ceramic assemblage (with an emphasis on drinking vessels) occurring around the mid-3rd millennium BC. In conclusion, an attempt is made to link these changes to major socio-political developments that took place in the northern Levant and upper Mesopotamia around the middle of the 3rd millennium BC.